2007
DOI: 10.1021/nl062964f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Avalanche Multiphoton Luminescence from Coupled Au Nanowires in the Visible Region

Abstract: We demonstrate highly efficient avalanche multiphoton luminescence (MPL) from ordered-arrayed gold nanowires (NWs) with low time-average excitation intensity, Iexc (5.0-9.1 kW/cm2). The intensity of avalanche MPL, IMPL, is about 10(4) times larger than that of three-photon luminescence, the slope partial differential log IMPL/ partial differential log Iexc of avalanche MPL reaches as high as 18.3, and the corresponding polarization dependence of IMPL has a form of cos50 phip. The emission dynamics of avalanche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 33 publications
4
69
0
Order By: Relevance
“…On the other hand, for the avalanche PL from the sample with d NW =18 nm, the PL emission intensity along the long axis of the NWs (b emi =0°) is smaller than the one perpendicular to the long axis (b emi =90°), the corresponding p parameter has a negative value of −0.12, which is different from the Au NW arrays with resonant excitation of LSPR (L NW < 1.5 μm) [17]. The unique emission polarization behavior of Ag NW arrays with L NW approximately 8 μm may be caused by the strong dipole-dipole interaction of TSPR of nearby NWs.…”
Section: Excitation Polarization Dependence Of the Pl From Ag Nw Arraysmentioning
confidence: 83%
See 2 more Smart Citations
“…On the other hand, for the avalanche PL from the sample with d NW =18 nm, the PL emission intensity along the long axis of the NWs (b emi =0°) is smaller than the one perpendicular to the long axis (b emi =90°), the corresponding p parameter has a negative value of −0.12, which is different from the Au NW arrays with resonant excitation of LSPR (L NW < 1.5 μm) [17]. The unique emission polarization behavior of Ag NW arrays with L NW approximately 8 μm may be caused by the strong dipole-dipole interaction of TSPR of nearby NWs.…”
Section: Excitation Polarization Dependence Of the Pl From Ag Nw Arraysmentioning
confidence: 83%
“…For the linear PL from the sample with d NW =120 nm, the peak PL intensity at the emission wavelength of 914 nm excited by p-polarized laser ða exc ¼ 0 ; E excitation to the SPR coupling between the nearby NWs for the avalanche PL from the NW arrays. But the avalanche PL of Ag NWs induced by single-photon absorption is less sensitive to the excitation polarization angle α exc than that of Au NWs induced by multiphoton absorption [17].…”
Section: Excitation Polarization Dependence Of the Pl From Ag Nw Arraysmentioning
confidence: 94%
See 1 more Smart Citation
“…Local surface plasmon resonance (LSPR) in the metal-dielectric composite nanostructures greatly enhances the local electric field [4][5][6]. These enhanced local electric fields can be used in many linear and nonlinear optical processes, such as surface-enhanced Raman scattering (SERS) [7], enhanced fluorescence emission of the adsorbed fluorescent materials [8], optical bistability [9], multiphoton luminescence [10], second harmonic generation [11], large third-order susceptibility [12], and photo-heat conversion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both the density of states and the field enhancement effects played important roles in the process of multiphoton-induced PL [26,28,29]. Recently, Wang et al [30] reported highly efficient avalanche multiphoton luminescence (MPL) from ordered-arrayed gold nanowires. However, MPL from Au:oxide composite films prepared by radio frequency (r.f.)…”
Section: Introductionmentioning
confidence: 99%